Modified voltage-mode controller for the quadratic boost converter with improved output performance - Jiang, Wentao (2019)
The control of the quadratic boost converter with unknown load resistance and where only the output voltage is used for feedback purposes is addressed. In the existing voltage-mode controlled converter system, there exists a performance `trade-off' between the transient responses after the onset of a reference input and a load disturbance due to the usage of the traditional proportional-integral control scheme. To overcome these problems, a modified voltage-mode controller is proposed. The proposed controller uses a normalised integral action in which the derivative of the integrand is bounded by a user-defined constant. The approximate stability analysis of the resultant voltage-mode controlled quadratic boost converter system is carried out to gain some insight into its closed-loop behaviour. Some simulation and experimental results comparing the performance of the proposed controller with that of the existing controller are also provided to show the improvements obtained using the proposed controller.